A comparison between fracture toughness at different locations of longitudinal submerged arc welded and spiral submerged arc welded joints of API X80 pipeline steels. (November 2015) - Chen, Xu; Lu, Hongsheng; Chen, Gang; Wang, Xin
Abstract: In this paper, extensively experimental testing of fracture toughness for two different welded joints of API X80 pipeline steels after service were carried out. The microstructures and CTOD resistance curves of longitudinal submerged arc welded (LSAW) and spiral submerged arc welded (SSAW) joints were investigated at different locations of the base metal (BM), weld metal (WM) and heat affected zone (HAZ). The critical fracture toughness values were compared with each other. The optical microscope (OM), scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) were used to analyze the fracture mechanism and precipitates composition. This investigation will provide an important reference to engineering practice and evaluation of pipeline structures.